Analisis Daya Saing Komoditas Kelapa di Kabupaten Kupang - Krisna Setiawan; Slamet Hartono; Any Suryantini (agriTECH, 2014)
Coconut cultivation in Kupang district have been exercised for generations in the Mamar (a kind of mixedcrop husbandry) and the garden (around the farm house). The farming was charactherized by inadequate adoption of the technical aspects of coconut farming, varying crop spacing, and without the use of fertilization. However, considering the size of the planting area and its production, the commodity still has the potency to be increased to have a high competitive value. This study was aimed to analyze the financial and economic profitability, competitive and comparative advantages of coconut commodity in Kupang district. The research method that used, as an indicator, to analyze the competitiveness was a descriptive method using the Policy Analysis Matrix (PAM). The results showed that, firstly, coconut farming in Kupang district did not have a competitive advantage which can be seen from the negative PP value and the PCR value that higher than 1 (one). However the farm had comparative advantages which can be seen from the positive value of SP and the DRC value that smaller than 1 (one). Secondly, the coconut commodity in Kupang district has a moderate competitive value and remained being able to be increased, for example by increasing the value-added of coconut processing.ABSTRAKPengusahaan tanaman kelapa di Kabupaten Kupang dilakukan secara turun temurun pada mamar dan sebagian lahan pekarangan. Penerapan aspek teknis usahatani kelapa belum memadai, jarak tanam tidak teratur dan tidak dilakukan pemupukan. Namun dilihat dari luas areal tanam dan produksi kelapa rakyat yang dihasilkannya, komoditas ini masih memiliki potensi untuk dikembangkan sehingga diharapkan memiliki daya saing tinggi. Penelitian ini bertujuan menganalisis profitabilitas finansial dan ekonomi, keunggulan kompetitif dan komparatif pada komoditas kelapa di Kabupaten Kupang. Metode penelitian yang digunakan sebagai indikator dalam menganalisis daya saing adalah metode deskriptif dengan menggunakan Policy Analysis Matrix (PAM). Hasil penelitian menunjukkan (1) usahatani kelapa di Kabupaten Kupang tidak memiliki keunggulan kompetitif dilihat dari nilai PP yang negatif dan PCR yang lebih besar dari satu. Namun memiliki keunggulan komparatif dilihat dari nilai SP yang positif dan DRC yang lebih kecil dari satu; (2) Komoditas kelapa di Kabupaten Kupang berdaya saing sedang dan masih dapat dikembangkan, salah satunya dengan cara meningkatkan nilai tambah dari pengolahan kelapa.